The prevalence of work-related stress, and its association with self-perceived health and sick-leave, in a population of employed Swedish women - Björkelund Cecilia; Dahlin-Ivanoff Synneve; Holmgren Kristina; Hensing Gunnel (BMC, 2009)
Abstract Background Women report more occupational ill-health and are more sick-listed than men. Exploration of women's working conditions would therefore seem to be valuable. In this study we investigated the prevalence of work-related stress and its association with self-perceived health and sick-leave in a population of employed, working Swedish women. Methods This cross-sectional population study comprised 424 employed, working women who answered questionnaires on work-related stress, self-perceived health and sick-leave. The odds ratio (OR) with 95% confidence interval (CI) was calculated in order to analyse the association between the exposure variables of work-related stress and outcome variables of ill-health symptoms, self-rated health and sick-leave. Results Ten percent of the group reported high perceived stress owing to indistinct organisation and conflicts, and 25% high perceived stress owing to individual demands and commitment. Twenty-two percent reported low influence at work and 33% reported work interference with leisure time. All categories of overall work-related stress were significantly associated with increased odds of high level of illness symptoms, with the highest OR for high perceived stress owing to indistinct organisation and conflicts and high perceived stress owing to individual demands and commitment with an OR of 3.17 (CI = 1.51-6.62) and 4.53 (CI = 2.71-7.56) respectively. High perceived stress owing to indistinct organisation and conflicts and low influence at work were significantly associated with sick-leave with an OR of 3.85 (CI = 1.59-9.30) and 2.54 (CI = 1.17-5.48) respectively. Conclusion This study showed an association between, on the one hand, work-related stress, and on the other hand, illness symptoms and sick-leave. Distinguishing between the occurrence of negative work characteristics, and the immediate perception of stress because of these, resulted in a broad view of women's working conditions and expanded knowledge of work-related stress in women.